1994
DOI: 10.1021/bi00206a014
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Components Neighboring the Conserved 518-533 Loop of 16S rRNA in 30S Subunits

Abstract: We report the synthesis of a radioactive, photolabile oligodeoxyribonucleotide probe complementary to 16S rRNA nucleotides 518-526 and its exploitation in identifying 30S ribosomal subunit components neighboring its target site in 16S rRNA. Nucleotides 518-526 lie within an almost universally conserved single-stranded loop that has been linked to the decoding region of Escherichia coli ribosomes. On photolysis in the presence of activated 30S ribosomes, the probe site-specifically incorporates into proteins S3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 43 publications
1
27
1
1
Order By: Relevance
“…One possible candidate for such a structure is the 530 stem-loop, one of the most highly conserved regions of the 16S rRNA molecule (44) and one whose secondary structure is influenced by interaction with S12 (45). Cross-linking studies have shown that this loop contacts S12 in E. coli (46), where rimO is present, yet intriguingly, the equivalent loop in 18S rRNA does not appear to contact S23 in humans (47), where rimO is absent. This hypothesis implies that only a stable S12-rRNA complex such as the assembled 30S ribosomal subunit (in which the surface to which S12 is bound is exposed to solution), and not free S12, can serve as an efficient substrate for RimO.…”
Section: Discussionmentioning
confidence: 95%
“…One possible candidate for such a structure is the 530 stem-loop, one of the most highly conserved regions of the 16S rRNA molecule (44) and one whose secondary structure is influenced by interaction with S12 (45). Cross-linking studies have shown that this loop contacts S12 in E. coli (46), where rimO is present, yet intriguingly, the equivalent loop in 18S rRNA does not appear to contact S23 in humans (47), where rimO is absent. This hypothesis implies that only a stable S12-rRNA complex such as the assembled 30S ribosomal subunit (in which the surface to which S12 is bound is exposed to solution), and not free S12, can serve as an efficient substrate for RimO.…”
Section: Discussionmentioning
confidence: 95%
“…Escherichia coli Q13 70S ribosomes and 30S and 50S subunits were prepared and activated as described earlier (Alexander et al 1994). ]-30S subunits with a 1.5 M excess of 50S subunits and purifying the labeled 70S ribosomes by fractionation following ultracentrifugation through a linear sucrose concentration gradient (15%-30%).…”
Section: Preparationsmentioning
confidence: 99%
“…Experiments designed to reconstitute the minimal ribosomal particle still capable of enzyme activity have established that L3 is essential for maintaining peptidyltransferase activity (15). A photolabile cDNA probe targeted to the central loop of domain V was shown to cross-link to L3 (26). With the use of a photolabile oligodeoxynucleotide probe complimentary to the ␣-sarcin region of E. coli, Muralikrishna et al (11) recently demonstrated the proximity of the ␣-sarcin region to domains IV and V of E. coli rRNA.…”
Section: Figmentioning
confidence: 99%